Influence of transplanting date and integrated weed management in system of rice intensification of aromatic black rice (Oryza sativa) - NONGMAITHEM, D; DOLIE, SIBINO; JAMIR, MOATOSHI; GOHAIN, TANKESWAR; LONGKUMER, TONGPANG; SINGH, AVANISH PRAKASH; TZUDIR, LANUNOLA; YADAV, REKHA; DUTTA, MANOJ (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during rainy seasons (kharif) of 2019 and 2020 at the research farm of School of Agricultural Sciences, Nagaland University, Nagaland to study the effect of transplanting date and weed management practices on productivity and profitability of aromatic black rice (Oryza sativa L.) under system of rice intensification. The experiment was conducted in a split plot design (SPD) with 3 transplanting dates (D1, 15th June; D2, 30th June; and D3, 15th July) in main plot and 5 weed managements practices [W1, Weedy check; W2, Conoweeding at 20 and 40 DAT (days after transplanting); W3, Pretilachlor @0.75 kg/ha (PE) fb hand weeding (HW) at 40 DAT; W4, Pretilachlor @0.75 kg/ha (PE) fb conoweeder at 40 DAT; and W5, Pretilachlor at 0.75 kg/ha (PE) fb bispyribac-sodium @ 25 g/ha (PoE)] in sub-plot, replicated thrice. Results showed that the most abundant weed flora observed in the experimental field were Fimbristylis quinquangularis (Vahl) Kunth, Cyperus esculentus (L.), Cyperus iria (L.), Rhynchospora colorata (L.) H.Pfeiff., Ludwigia linifolia Poir, Mimosa pudica (L.), Mimosa diplotricha Sauvalle, Scoparia dulcis (L.) and Eriochloa villosa (Thunb.) Kunth. Transplanting on 15th June recorded highest growth and yield of black rice. The improvement in the grain yield was about 39% under 15th June over 15th July transplanting date. Among weed management practices, pretilachlor @0.75 kg/ha at 3 DAT fb HW at 40 DAT recorded minimum density of weeds resulting in higher growth attributes and yield of black rice. Economic analysis showed that highest benefit cost (B:C) ratio was obtained when black rice was transplanted on 15th June along with application of pretilachlor @0.75 kg/ha at 3 DAT fb bispyribac-sodium @25 g/ha at 20 DAT and demonstrated to be the best treatment for profitable production of black rice under system of rice intensification.